The challenges of being a female pastor: A case of the Apostolic Faith Mission in Zimbabwe - Mupangwa, Terence (HTS teologiese studies, 2020)
The focus of this article is to highlight some of the inherent gender injustices experienced by the female pastors within the Apostolic Faith Mission in Zimbabwe (AFMZ). Drawing insights from the field research conducted in pursuance of a doctoral programme, the study foregrounds some of the barriers that women have had to endure when it comes to the issue of being ordained as a pastor. The article also interrogates the reasons used as a basis to exclude female pastors from the key decision-making bodies and to deny them the opportunity to preach at the national conference, which is the biggest gathering within the AFMZ. This is a qualitative study utilising interviews, focus group discussions and the observation method. The main findings emerging from this study reveal that whilst some positive changes have been made towards the inclusion of women in the pastoral ministry, however, there are still many gaps needing urgent attention before the AFMZ becomes a gender-inclusive and gender-equitable faith community.Contribution: This article foregrounds the challenges faced by female pastors in the AFMZ. It advocates for gender mainstreaming and gender inclusive policies in the AFMZ leadership structures. This is in sync with the focus of this collection, for which the main thrust is on women and religious leadership.